Bioadhesives: Current hotspots and emerging challenges. (June 2021) - Zhu, Haofang; Tian, Jiang; Mao, Hongli; Gu, Zhongwei
Abstract: Bioadhesives have gained wide attention because of their obvious advantages over conventional sutures such as easy operation, noninvasive sealing, and immediate hemostasis. At present, a variety of commercial medical tissue adhesives based on various materials have been developed to replace or assist sutures in the application of repair and regeneration of heart, blood vessels, lungs, and other soft tissues. However, existing tissue adhesives are usually either cytotoxic, fragile, or lacking adhesive strength. Therefore, significant research endeavors have been focused on developing a safe and effective tissue adhesive to overcome these problems. In this review, we introduce the current hotspots and recent progress of bioadhesives; the future research direction and prospect of bioadhesives are proposed as well.